Knowledge-sharing hostility, knowledge manipulation, and new product development performance - Cai, Ruilin; Ma, Yingshuang (Frontiers in Psychology, 2022)
New product development is an important driver for enterprise sustainable development. It is necessary to promote the knowledge sharing of heterogeneous individuals such as design, technology, market and sociologists. This paper discusses the influence of negative individual knowledge management from the perspective of knowledge sharing hostility and knowledge manipulation on the performance of new product development. To examine our hypotheses, we conducted a questionnaire survey to 438 employees in China. The results show that although knowledge manipulation contributes to individual innovation performance, it has an inverted U-shaped curve relationship with the team’s product development performance. The hostility of knowledge sharing induces knowledge manipulation, which indirectly influences the performance of new product development. The coordination flexibility of R&D team positively moderates the impact of knowledge manipulation on new product development. Implications and future research directions are discussed.